Global Englishes Awareness and Pedagogical Practices: A Study of Chinese English Teacher Educators - Liu, Junshuan (OKARA: Jurnal Bahasa dan Sastra, 2023)
Previous studies on Global Englishes (GE) awareness tend to focus on pre- and in-service English teachers, with little attention paid to English teacher educators. Given the potential transfer of English teacher educators’ perceptions on diverse Englishes and associated teaching practices to English teacher trainees, this study adopted a mixed-methods approach to investigate the GE awareness and pedagogical practice of Chinese English teacher educators who are engaged in preparing English teachers for junior middle schools in rural China. The analysis of the data collected via a questionnaire survey with 49 English teacher educators and interviews with seven of them indicates that most participants had a pseudo GE awareness, holding a positive attitude toward non-native English but deeming it as less standard than its native counterpart, and almost all participants followed the native-speakerist paradigm in classroom teaching, and did not actively introduce GE to their students. Revealed simultaneously is that even the participants with long stays overseas also bought into native speakerism. In reference to China’s socio-cultural and historical-political contexts, this study proposes that China adjust its national English syllabi and reconstruct the professional development programs for English teacher educators to facilitate the implementation of Global Englishes Language Teaching (GELT).